Fabrication and hardness of in-situ Al3Ti–Al2O3 composite - Duong, Binh N.; Do, Binh T.; Dang, Dung D.; Tran, Huy D. (Frontiers in Materials, 2023)
In this work, an in-situ Al3Ti-Al2O3 composite was optimally synthesized from raw powders via mechanical milling and conventional sintering processes. The strong influence of milling time on the promotion of the phase reaction between the initial TiO2 and Al materials was proven by using X-ray diffraction and surface morphology analysis. The obtained results showed that the milling process did not initiate any reaction between the raw TiO2 and Al materials. However, the milling process was important for creating a homogeneous powder mixture and refining the particle size of the powders. The Al3Ti-Al2O3 composites were completely formed after conventional sintering at 750 °C for 30 min for a milling time of over 4 h. The highest obtained microhardness of the composite was approximately 130 HV, which was suggested to be related to the microstructure of the bulk composite specimen consisting of two main phases, the Al3Ti matrix and the Al2O3 particles dispersed in the matrix. A small portion of an unidentified phase, a Ti-rich compound, was found in the matrix together with a tiny fraction of AlTi3. We suggest that the optimal sintering process and mechanical milling are important key factors in fabricating bulk hardness Al3Ti-Al2O3 composite materials.